Loss of dominant caterpillar genera in a protected tropical forest - Salcido, Danielle M. (Sci Rep, 2020)
Reports of biodiversity loss have increasingly focused on declines in abundance and diversity of insects, but it is still unclear if substantive insect diversity losses are occurring in intact low-latitude forests. We collected 22 years of plant-caterpillar-parasitoid data in a protected tropical forest and found reductions in the diversity and density of insects that appear to be partly driven by a changing climate and weather anomalies. Results also point to the potential influence of variables not directly measured in this study, including changes in land-use in nearby areas. We report a decline in parasitism that represents a reduction in an important ecosystem service: enemy control of primary consumers. The consequences of these changes are in many cases irreversible and are likely to be mirrored in nearby forests; overall declines in the region will have negative consequences for surrounding agriculture. The decline of important tropical taxa and associated ecosystem function illuminates the consequences of numerous threats to global insect diversity and provides additional impetus for research on tropical diversity.